2022
DOI: 10.1080/14999013.2021.1963016
|View full text |Cite
|
Sign up to set email alerts
|

The Meaningfulness of Grandiose and Vulnerable Narcissism in Forensic Mental Health Rehabilitation Practice: A Systematic Review

Abstract: Narcissism is a personality construct with grandiose, and vulnerable aspects, that are interconnected through antagonistic characteristics. While antagonism is strongly related to antisocial behavior, the role of narcissism remains underexplored in offender rehabilitation practice. Research in non-forensic samples has already shown promising results in the differential associations for grandiose and vulnerable narcissism in relation to violent and antisocial behavior and treatment responsiveness that could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Grandiose narcissists were violent when triggered by threats to their self-esteem, while for those high in vulnerable narcissism, explosive anger episodes were triggered by fears of abandonment ( Green & Charles, 2019 ). Moreover, a meta-analysis examining differences in narcissism types in forensic rehabilitation found that grandiose narcissism was correlated to proactive violence whereas vulnerable narcissism was correlated to reactive violence mediated by impulsivity and distressing emotions ( Keune et al, 2021 ). Together this research aligns with this review’s finding that the strength of the relationship between IPV perpetration differs significantly between grandiose and vulnerable narcissism but this is likely moderated by different precipitating factors of the IPV perpetrated by grandiose and vulnerable narcissists; future research should explore this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grandiose narcissists were violent when triggered by threats to their self-esteem, while for those high in vulnerable narcissism, explosive anger episodes were triggered by fears of abandonment ( Green & Charles, 2019 ). Moreover, a meta-analysis examining differences in narcissism types in forensic rehabilitation found that grandiose narcissism was correlated to proactive violence whereas vulnerable narcissism was correlated to reactive violence mediated by impulsivity and distressing emotions ( Keune et al, 2021 ). Together this research aligns with this review’s finding that the strength of the relationship between IPV perpetration differs significantly between grandiose and vulnerable narcissism but this is likely moderated by different precipitating factors of the IPV perpetrated by grandiose and vulnerable narcissists; future research should explore this.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, future research should examine mediators and moderators of the relationships between grandiose as well as vulnerable narcissism and IPV perpetration. Given the different unique and complex traits of these types of narcissism, violence perpetrated by those with each trait may be influenced by a third variable such as impulsivity ( Keune et al, 2021 ), or attachment ( Buck et al, 2014 ). Rinker (2010) argued that physical IPV perpetration and controlling behaviors are mediated by the subtypes of narcissism and thus, it is necessary for research to differentiate between these traits.…”
Section: Discussionmentioning
confidence: 99%